2023
DOI: 10.1021/acs.jafc.3c00442
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Food Factors and Processing on Protein Digestibility and Gut Microbiota

Abstract: Protein is an essential macronutrient. The nutritional needs of dietary proteins are met by digestion and absorption in the small intestine. Indigestible proteins are further metabolized in the gut and produce metabolites via protein fermentation. Thus, protein indigestibility exerts a wide range of effects on gut microbiota composition and function. This review aims to discuss protein digestibility, the effects of food factors, such as protein sources, intake level, and amino acid composition, and making meat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 179 publications
0
3
0
Order By: Relevance
“…Vendl et al suggested that long-chain PFAS form stronger biochemical bonds with fish muscle proteins than short-chain PFAS. Muscle proteins may undergo changes after cooking (e.g., steaming, grilling, and oil-frying) such as protein aggregation, cross-linking, muscle oxidation, or disulfide bond formation, all of which increase the resistance of proteins to digestive enzymes. ,, As a result, long-chain PFAS that bind more strongly to proteins is more difficult to extract from denatured proteins during digestion. Similarly, Girard et al found that methylmercury, which has protein affinity, was reduced to 12.6 ± 5.6% of control values after cooking.…”
Section: Resultsmentioning
confidence: 99%
“…Vendl et al suggested that long-chain PFAS form stronger biochemical bonds with fish muscle proteins than short-chain PFAS. Muscle proteins may undergo changes after cooking (e.g., steaming, grilling, and oil-frying) such as protein aggregation, cross-linking, muscle oxidation, or disulfide bond formation, all of which increase the resistance of proteins to digestive enzymes. ,, As a result, long-chain PFAS that bind more strongly to proteins is more difficult to extract from denatured proteins during digestion. Similarly, Girard et al found that methylmercury, which has protein affinity, was reduced to 12.6 ± 5.6% of control values after cooking.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it is well documented that food intake possesses modulatory effects on the gut microbiota. For instance, protein intake, digestion, and absorption affect the composition and function of microbiota [ 61 ]. Moreover, food intake was found to increase serum melatonin levels, which makes food a noteworthy regulator of circadian rhythm.…”
Section: Melatonin and Gm Interplaymentioning
confidence: 99%
“…Protein molecules expand and lose their natural structure at high temperatures resulting in changes in texture, taste and digestion heat on the other hand can increase the digestibility of particular proteins, thereby rendering them more absorbable. The Maillard reaction which happens during high-temperature cooking can result in the creation of proteinlysine and protein-arginine adducts [19]. This reaction can cause browning of food items changes in taste as well as modifications in digestibility of proteins and allergies, extrusion processing is commonly used to manufacture snack foods and breakfast cereals [35].…”
Section: Effects Of Processing On Proteinsmentioning
confidence: 99%